PERANCANGAN VIDEO PROFILEBATIKTANAH LIEK KHAS MINANGKABAUDI SAWAHAN DALAM PADANG - Muhammad Arif Saputra,; syafwandi syafwandi; san ahdi (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The purpose of designing this Liek batik video profile is as a medium of socialization to the public. So that people both inside and outside West Sumatra know the culture and crafts in West Sumatra. The communication media used to socialize and promote liek batik is a video profile in the form of a documentary, which will later tell the history and origins of liek batik in West Sumatra. This liek batik was re-introduced by Wirda Hanim in 1994, located at Jl. Sawahan In Padang. Data collection is done by interview, observation and documentation. Analysis of the data used is the analysis of 5W + 1H (what, who, where, when, why and how). The results of the design as the main media video and supporting media in the form of calendars, mugs, posters, CD covers and labels, opening bumper In / Out, T-shirts, shopping bags.Keywords: Design, Video Profile, Batik Tanah Liek.